2023
DOI: 10.3390/children10061010
|View full text |Cite
|
Sign up to set email alerts
|

School and Bicultural Factors as Mediators between Immigrant Mothers’ Acculturative Stress and Adolescents’ Depression in Korea

Abstract: In Korea, marriages between Korean men and foreign women have surged since the late 1990s, resulting in public interest in the psychosocial adjustment of their children. This study examined the mediating effects of immigrant mothers’ school involvement, adolescents’ school adjustment, and bicultural acceptance on the relationship between the mothers’ acculturative stress and adolescents’ depression, as well as whether the structural relationships differed by the sex of adolescents. Data were collected from 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 70 publications
1
5
1
Order By: Relevance
“…Some research findings have indicated that parental involvement in education declines in terms of amount or effectiveness during middle school because adolescents may perceive such parental involvement in schools as interference with their autonomy [25]. In contrast, parental involvement in education was found to be positively associated with student achievement, school adjustment, and social relationships in middle school in previous studies [24,26,27].…”
Section: Maternal Involvement In Education and Adolescents' School Ad...mentioning
confidence: 96%
See 4 more Smart Citations
“…Some research findings have indicated that parental involvement in education declines in terms of amount or effectiveness during middle school because adolescents may perceive such parental involvement in schools as interference with their autonomy [25]. In contrast, parental involvement in education was found to be positively associated with student achievement, school adjustment, and social relationships in middle school in previous studies [24,26,27].…”
Section: Maternal Involvement In Education and Adolescents' School Ad...mentioning
confidence: 96%
“…The relationship is not necessarily simply unidirectional. Several studies [27,48,49] have verified the effect of school life on bicultural acceptance by indicating that higher school adjustment predicts higher bicultural acceptance among adolescents from multicultural families.…”
Section: Reciprocal Relationships Between School Adjustment and Bicul...mentioning
confidence: 99%
See 3 more Smart Citations